Tourism of cultural events and festivals. Contrast of experiences between two film festivals in different phases of consolidation: San Sebastián (Spain) and Fajr (Iran) - Dezfoulian, Dorsa (Revista de Estudios Andaluces, 2024)
Tourism is an important economic phenomenon in both developed and developing countries. Event tourism, specifically centered on cultural activities, is a niche market that has been gaining importance and has been researched for the last thirty years. There is remarkable agreement in the scientific literature that cultural events have a significant positive impact on the deseasonalization and rejuvenation of a tourist destination while promoting local culture. Among the most popular cultural events in the world, film festivals constitute a distinct modality. This article is focused on contrasting two festival experiences with different levels of consolidation, San Sebastian (Spain) and Fajr (Iran), analyzing their main features and differences from a tourism point of view. The first one has achieved worldwide prestige; while the second one is still in a consolidation phase, in an institutional and socioeconomic context comparable to the one the Spanish festival went through several decades ago. The article tries to point out the main shortcomings and challenges that the Fajr Festival must face, especially in the coordination of the venues and the corresponding sectors of the festival, in order to advance towards a high-level event with a touristic value that can benefit the locals and open the doors towards international tourism.